2006
DOI: 10.1080/00016480500416819
|View full text |Cite
|
Sign up to set email alerts
|

Cervical bronchogenic cyst: asymptomatic neck mass in an adult male

Abstract: Bronchogenic cysts are rare congenital malformations of ventral foregut development. They are usually located in the mediastinum and intrapulmonary regions. Localization in the cervical area is unusual and the majority of cases reported have been found in the pediatric population: the literature reports few cases in adults. We describe a 57-year-old male who presented an asymptomatic right lateral neck mass. Diagnostic studies included chest X-ray, pharyngo-esophagus double-contrast X-ray, computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 15 publications
1
47
0
1
Order By: Relevance
“…When the duplication or separation of the notochord is incomplete, ectopic cysts are generated and present the characteristics of any part of the foregut. 4 It is difficult to diagnose spinal bronchogenic cyst before surgery and the final diagnosis depends on the pathological examination. A research confirmed that six cell types were identified, including ciliated cells, nonciliated cells, goblet cells, basal cells, Kulchisky's cells and undifferentiated cells, which were similar to the human bronchial epithelium of the upper respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the duplication or separation of the notochord is incomplete, ectopic cysts are generated and present the characteristics of any part of the foregut. 4 It is difficult to diagnose spinal bronchogenic cyst before surgery and the final diagnosis depends on the pathological examination. A research confirmed that six cell types were identified, including ciliated cells, nonciliated cells, goblet cells, basal cells, Kulchisky's cells and undifferentiated cells, which were similar to the human bronchial epithelium of the upper respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports of SBCs suggested that the lesions enlarge slowly and lead to pain, numbness, weakness of limbs or back and even paralysis when they compress the nerve roots or spinal cord. [3][4][5][6][7][8] None of the complications secondary to ruptured cysts were reported, such as chemical meningitis, abscess formation, and hydrocephalus. It is difficult to make the correct diagnosis before surgery due to its extremely low morbidity and non-typical signs, symptoms and imaging findings.…”
Section: Introductionmentioning
confidence: 99%
“…Needless to say that in case of malignant change, resection of the cyst by open procedure is probably a more oncologically acceptable operation [2,3]. The rare intraoperative complication of fatal air embolism has not been described in open surgery [4]. Yoshida et al reported a case with tracheal wall damage while performing sharp separation of the cystic wall from the trachea with thoracoscopic surgery [11].…”
Section: Discussionmentioning
confidence: 99%
“…They usually present on the right side of the neck and they are extremely rare in adults [1]. Its prophylactic excision leads to excellent outcome [2][3][4]. We present a case of a bronchial cyst that presented as a left lateral cervical mass mimicking cystic thyroid nodule in an adult.…”
Section: Introductionmentioning
confidence: 98%
“…in the lung parenchyma [15][16][17][18]. Besides these typical and well-known locations for BCs, review of literature reveals some other less common locations: BCs can be atypically located in the neck [20], in the skin [19] and in the pericardium [21]. Subdiaphragmatic locations are extremely rare: In some cases BCs are discovered in the retroperitoneum [22] and in the abdominal cavity [17].…”
Section: Cysts Derived From the Primitive Foregutmentioning
confidence: 99%